Factors associated with stroke recurrence and mortality in ischemic and haemorrhagic stroke: Protocol for a systematic review and meta-analysis - Simone Ryan; Katie Robinson; Rose Galvin; Margaret O’Connor; John McCabe; Eleanor Fallon; Sara Hayes (PLoS ONE, 2025)
Background and objectives Stroke is one of the leading causes of death and disability worldwide. People with stroke face a significant risk of recurrence, however, there is a lack of consensus on the risk factors for stroke recurrence. Previous systematic reviews in this area are either outdated, focus exclusively on clinical risk factors, or are limited by geographical region, stroke subtype or age group. This review aims to systematically identify clinical and lifestyle risk factors associated with stroke recurrence and mortality in people with stroke. Methods A systematic search will be conducted in four electronic databases (PubMed, EMBASE, CINAHL and PsycINFO) and grey literature sources. Only prospective cohort studies that estimate the association between risk factors and stroke recurrence and/or mortality in adults with ischemic and haemorrhagic stroke will be included. The exposures of interest are clinical and lifestyle risk factors, including vascular and cardiac factors such as hypertension or atrial fibrillation, and behavioural factors such as physical activity, nutrition, or smoking. Two independent reviewers will conduct screening, data extraction, and risk of bias assessment using the ROBINS-E tool, while the GRADE approach will be used to evaluate the certainty of evidence. A meta-analysis using a random-effects model will be used to determine the overall effect for each exposure on stroke recurrence and/or mortality. However, if a meta-analysis is not justified, a narrative synthesis will instead be conducted. Discussion Recurrent strokes are associated with greater mortality and poorer functional prognosis than first-time events, imposing greater economic burden on healthcare services. This review will identify factors that increase one’s risk for recurrence, thereby informing the development and refinement of clinical guidance for secondary stroke prevention; a key priority for both those living with stroke and the wider health service.